2021
DOI: 10.1002/job.2573
|View full text |Cite
|
Sign up to set email alerts
|

Unaccounted for no more: Explicating managers' role in accountability enactment

Abstract: Accountability research has focused primarily on how subordinates perceive or react to workplace accountabilities and largely ignored how managers choose to enact it. This omission has occurred despite repeated claims that managers hold subordinates accountable to different degrees and in different ways. We conducted a systematic review of accountability research for insights into managers' role in, and differential application of, workplace accountability. Through this review, we inductively developed a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The limited body of empirical work on accountability in HR processes has considered accountability through the mechanisms by which individuals are held accountable, including performance appraisal, disciplinary procedures, and employment contracts (Brees & Ellen III, 2022;Ferris et al, 1995Ferris et al, , 1997Frink & Klimoski, 2004). For example, Castilla (2015) found that measures to increase accountability in performance-related reward decisions reduced the gender pay gap, indicating that accountability encouraged consistency in pay decisions.…”
Section: Felt Accountability In Hr Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited body of empirical work on accountability in HR processes has considered accountability through the mechanisms by which individuals are held accountable, including performance appraisal, disciplinary procedures, and employment contracts (Brees & Ellen III, 2022;Ferris et al, 1995Ferris et al, , 1997Frink & Klimoski, 2004). For example, Castilla (2015) found that measures to increase accountability in performance-related reward decisions reduced the gender pay gap, indicating that accountability encouraged consistency in pay decisions.…”
Section: Felt Accountability In Hr Implementationmentioning
confidence: 99%
“…Feelings of accountability are informed by a wide range of factors including characteristics of the environment, of the actor themselves, and of observers or recipients of the accountability‐driven action (Frink et al, 2008). Individuals therefore form their feelings of accountability based on formal and informal cues about the context of the situation and norms of behavior from their environment (Brees & Ellen III, 2022; Frink & Klimoski, 1998). While many factors drive feelings of accountability, we take inspiration from Schlenker et al's (1994) triangle model of responsibility to explain the focus of line managers' felt accountability.…”
Section: Accountability and Line Manager Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…They develop an integrative conceptual framework to explain the effects of contemporary career attitudes and conducted a comprehensive meta-analysis to examine the outcomes associated with these career attitudes. Next,Brees and Ellen (2022) conducted a systematic review of the accountability literature to examine managers' role in, and differential application of, workplace accountability. Based on this, they developed a model of managerial accountability enactment, highlighting how managers decide to enact accountability.…”
mentioning
confidence: 99%